Example-Based Learning in Computer-Aided STEM Education - Gulwani, Sumit (Communications of the ACM, 2014)
Human learning and communication is often structured around examples, possibly a student trying to understand or master a certain concept through examples or a teacher trying to understand a student’s misconceptions or provide feedback through example behaviors. Example-based reasoning is also used in computer-aided programming to analyze programs, including to find bugs through test-input-generation techniques and prove correctness through inductive reasoning or random examples15 and synthesize programs through input/output examples or demonstrations.